A case of Brooke-Spiegler syndrome with a novel germline deep intronic mutation in the CYLD gene leading to intronic exonization, diverse somatic mutations, and unusual histology - Kazakov, Dmitry V; Thoma-Uszynski, Sybilla; Vaněček, Tomáš; Kacerovská, Denisa; Grossmann, Petr; Michal, Michal (The American journal of dermatopathology, 2009)
We present a case of Brooke-Spiegler syndrome with a germline deep intronic mutation in the CYLD gene leading to intronic exonization. Additionally, diverse somatic mutations were identified, namely loss of heterozygosity, a recurrent nonsense mutation, and a sequence mutation causing exon skipping. These somatic aberrations were identified in 4 different cylindromas that had been removed from the patient. Additionally, we microscopically studied a spiradenocylindroma that showed unusual histology, including foci of follicular differentiation. A deep intronic mutation resulting in exonization and a somatic sequence mutations causing exon skipping are hitherto unreported genetic mechanisms involving the CYLD gene in patients with Brooke-Spiegler syndrome.
Keywords: syndrom; adenoidně cystický karcinom; Carcinoma, Adenoid Cystic; lidé středního věku; lidé; ženské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; Exons; Introns; mutace; Female; Loss of Heterozygosity; Syndrome; exony; mutační analýza DNA; Middle Aged; Reverse Transcriptase Polymerase Chain Reaction; práce podpořená grantem; Tumor Suppressor Proteins; Mutation; Humans; Research Support, Non-U.S. Gov't; nádorové supresorové proteiny; introny; DNA Mutational Analysis; Skin Neoplasms; nádory kůže; ztráta heterozygozity